The Tradition Of Dowry And Gender Equality Issues: A Literature Review - Vicente Manuel Luis Guterres; Anak Agung Istri Ngurah Marhaeni; Made Heny Urmila Dewi; Made Dwi Setyadhi Mustika (Riviera Publishing, 2024)
Dowry is a tradition that has existed for a long time and exists in many cultures around the world, including in Indonesia. Although dowry has symbolic and cultural significance, this tradition can cause several problems, especially related to gender equality. The purpose of this study is to compare the practice of dowry that applies in several countries and to examine the relationship between dowry practices and gender equality issues. This study uses a qualitative approach with data collection techniques through observation of various relevant literature, with descriptive analysis techniques. The results of the study show that the practice of dowry in several countries has differences where there are countries that practice dowry or dowry given from the woman's to the man's side, or the man's to the woman's side. In addition, there are countries that practice dowry given by the man or woman individually, which is used for the business capital of a new family that is formed. The results of the study also show that the practice of dowry in several countries reflects gender inequality that is still deeply rooted in patriarchal culture. This reduces women's autonomy and strengthens the power imbalance in marital relationships. Despite international efforts such as the Convention on the Elimination of All Forms of Discrimination against Women that seek to address this discrimination. Therefore, it is important to eliminate the practice of dowry that is not in accordance with the principle of gender equality in order to promote a fairer and healthier marriage relationship.